Financial Crises and Banking Governance in the Emerging Countries of South East Asian (Global Journal of Management and Business Research, 2017)
This article aims to analyze the effectiveness of bank governance mechanisms or through prudential regulation as an external dimension or either the mode of administration as an internal dimension is a source of birth of crises. In addition, the risk in terms of financial instability, institutional weaknesses and the weakness of regulatory and supervisory system leads to a lack of governance in banks. This empirical study was conducted on a sample of four emerging countries of South East Asia and to an annual period from 1980 to 2010, using the Probit model on panel data. The results also suggest that there is a strong and significant causal relationship between financial crises and bank governance in the South East Asian countries during periods of financial liberalization.
Keywords: financial crises; bank governance; financial liberalization; south east asian countries; probit panel data